2006
DOI: 10.1016/j.jacc.2005.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coronary Artery Bypass Surgery With Percutaneous Coronary Intervention With Drug-Eluting Stents for Unprotected Left Main Coronary Artery Disease

Abstract: Despite a higher percentage of high-risk patients, PCI with DES for ULMCA disease was not associated with an increase in immediate or medium-term complications compared with CABG. Our data suggest that a randomized comparison between the two revascularization strategies for ULMCA may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
171
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(195 citation statements)
references
References 24 publications
18
171
2
4
Order By: Relevance
“…[3][4][5][6][7][8][9][10] In our study location of the lesion was distal in 70 (68.6%) patients.In a study by Saeed Sadeghian et al showed that the proportion of the male sex in those with LMS was higher than that of the ones without LMS stenosis (87.8% vs. 71.4%, P=0.020) and that patients with LMS stenosis were older (mean age of 58.8±10.5 years in those with LMS stenosis vs. 55.6±9.2 in the ones without LMS, P=0.03).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] In our study location of the lesion was distal in 70 (68.6%) patients.In a study by Saeed Sadeghian et al showed that the proportion of the male sex in those with LMS was higher than that of the ones without LMS stenosis (87.8% vs. 71.4%, P=0.020) and that patients with LMS stenosis were older (mean age of 58.8±10.5 years in those with LMS stenosis vs. 55.6±9.2 in the ones without LMS, P=0.03).…”
Section: Discussionsupporting
confidence: 43%
“…LMS stenosis currently occurs in 4% to 6% of all patients undergoing coronary angiography (CAG) 1 and in 30% of coronary artery bypass grafting (CABG) 2 patients. LMS stenosis occurs as an isolated lesion in 6% to 9% of patients, whereas over 70% to 80% ofpatients also have multi vessel coronary artery disease (CAD) [3][4][5][6][7][8][9][10] .As, LMS stenosis has high risk of restenosis.11 So, traditionally, CABG is the treatment of LMS coronary artery stenosis. However, drawbacks include multiple vascular anastomoses (which consume bypass conduits and can lead to complications), permanent occlusion of the LMS coronary artery, 1 and less physiologic retrograde myocardial perfusion.…”
mentioning
confidence: 99%
“…[10][11][12] Studies comparing PCI involving drugeluting stents with CABG have generally been smaller and nonrandomized. [13][14][15][16][17][18][19][20][21][22][23][24] Data from randomized, controlled trials of drug-eluting stents as compared with bare-metal stents have shown significant reductions in the rate of repeat intervention, with similar rates of death and myocardial infarction. 25 These improvements have led to expanded use of PCI in patients with complex coronary anatomical features, though most randomized trials comparing drugeluting stents and bare-metal stents excluded such patients.…”
mentioning
confidence: 99%
“…[147][148][149] Several studies comparing CABG to PCI, however, indicated that the advantage of CABG consists primarily of fewer repeat revascularizations. 139,[149][150][151][152][153][154][155] The study by Brener et al 156 indicates no significant mortality difference between PCI and CABG after 3 years of follow-up. Longer-term follow-up is needed.…”
Section: Recommendations For Pci For Unprotected Left Main Coronary Amentioning
confidence: 99%